HUBUNGAN ANTARA KEMAMPUAN BERBICARA SISWA DAN MOTIVASI KERJA DENGAN KESIAPAN MEREKA DALAM MEMASUKI TENAGA KERJA - D. Aris Sudarsono (Sekolah Tinggi Pastoral Kateketik (STPKat) Santo Fransiskus Assisi Semarang, 2022)
A person's readiness to enter the world of work after they finish vocational secondary education is not systematically prepared by educational institutions. at SMK Antonius Semarang. This research is a quantitative research design. The data collection technique that the author uses; documentation, observation and tests. After the data on students' speaking ability and work motivation were collected, the data were calculated statistically to determine the relationship between the two variables. They are the independent variable (X) and the dependent variable (Y), the independent variables are speaking ability and work motivation and the dependent variable is being included in the workforce. The results showed that students' speaking ability significantly affected their readiness to enter the world of work as evidenced by the results of the T test for 14,892 which was greater than the t table (1,98) and had an effect of 71,1%. Work motivation has a significant effect simultaneously on their readiness to enter the world of work, as evidenced by the results of the T test of 33. 068 which is greater than the t table (1.98) and has an effect of 92.4%. While the results of students' speaking ability and motivation have a significant effect on working simultaneously on their readiness to enter the world of work as evidenced by the F test of 600.67 which is greater than F table (3.10) and has an effect of 92.4%.